Impromptu Drama: Human Flourishing among Children and Young Adults with Cerebral Palsy - Jeanette Bresson Ladegaard Knox (Nordic Journal of Arts, Culture and Health)
Purpose: The pilot project Face2Face (F2F) explores the potential for self-acceptance, community building, and human growth through improvisational theater with children and young adults with cerebral palsy (CP). Method: Drawing on ethnography at a private foundation for individuals with CP, the author observed and occasionally partook in activities exploring drama-based methods, such as improvisation, with three children and four young adults. The author had informal conversations with all participants and conducted interviews with two parents. Findings: Drama and music in the form of improvisation can lead to greater courage to self-express and a sense of belonging to a community. Improvisation gradually unlocked participants’ imagination, expanding their feeling of what was possible for them. Findings also suggest that improvisation can give family and audience members greater understanding of life with CP. Value: Exploring impromptu drama can support people with CP by emphasizing individual human resources.